Papua New Guinean literature: A unique narrative under multiculturalism - Yang, Yan; Pei, Zhengwei (American Journal of Social Sciences and Humanities, 2025)
The purpose of this paper is to explore the dynamic evolution of Papua New Guinean literature amid the collision and fusion of its indigenous traditions and diverse foreign cultural elements, and to further clarify how this literature articulates authentic indigenous voices and constructs a distinct national identity within a complex multicultural context. To achieve this goal, the paper adopts a literature research method: it systematically collects and analyses academic papers, literary monographs, and critical reviews related to Papua New Guinean literature, and based on this, conducts an in-depth analysis of three core dimensions of the literature—its historical development process from oral traditions to written works, representative authors and their works, and its evolutionary path under the dual influence of Western and Eastern cultures. The study finds that Papua New Guinean literary tradition not only vividly mirrors the country’s societal transformations and inherent national ethos but also plays a pivotal role in preserving, inheriting, and promoting indigenous cultures in the age of globalization. Furthermore, the practical implications are that this research on Papua New Guinean literature is expected to offer novel perspectives for understanding the diversity and unique value of Pacific Island literature as a whole, thereby enriching regional literary studies and providing references for the exploration of indigenous literary identities in global multicultural contexts.